2021
DOI: 10.3390/ijerph18083872
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Proxy-Reported Life-Space Assessment in Institutionalized Settings (LSA-IS-Proxy) for Older Persons with and without Cognitive Impairment

Abstract: (1) Background: Life-space mobility assessments for institutionalized settings are scarce and there is a lack of comprehensive validation and focus on persons with cognitive impairment (CI). This study aims to evaluate the psychometric properties of the Life-Space Assessment for Institutionalized Settings by proxy informants (LSA-IS-proxy) for institutionalized, older persons, with and without CI. (2) Methods: Concurrent validity against the self-reported version of the LSA-IS, construct validity with establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Most information was provided for the validity of the LSM questionnaires, more specifically for their construct validity showing predominantly hypothesisconfirming associations with physical, cognitive, psychosocial, financial, environmental, and/or sociodemographic variables. Given the overall complexity of real-life mobility [4], it was unexpected that only a few of the identified studies assessed the construct validity of the LSM questionnaires based on a conceptual framework of mobility including various potential determinants [21][22][23]48]. Summarizing the results on construct validity of the same questionnaire across several studies, the UAB-LSA, the NHLSD, the LSA-CI and the interview/proxy-based LSA-IS were identified as the most valid questionnaires for the LSM construct.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most information was provided for the validity of the LSM questionnaires, more specifically for their construct validity showing predominantly hypothesisconfirming associations with physical, cognitive, psychosocial, financial, environmental, and/or sociodemographic variables. Given the overall complexity of real-life mobility [4], it was unexpected that only a few of the identified studies assessed the construct validity of the LSM questionnaires based on a conceptual framework of mobility including various potential determinants [21][22][23]48]. Summarizing the results on construct validity of the same questionnaire across several studies, the UAB-LSA, the NHLSD, the LSA-CI and the interview/proxy-based LSA-IS were identified as the most valid questionnaires for the LSM construct.…”
Section: Discussionmentioning
confidence: 99%
“…Completion times were provided even less frequently, averaging between 3 min and 9 min across 5 studies [16,21,22,27,48 . Four studies used a conceptual framework for mobility [4] to select constructvariables [21][22][23]48]. Overall, results on construct validity yielded expected directions and magnitudes of correlations with cut-offs of r > 0.5 for similar (e.g., physical variables) and r > 0.30-0.50 for related constructs (e.g., financial, psychosocial variables) for evaluation.…”
Section: Feasibilitymentioning
confidence: 92%
See 3 more Smart Citations